Alveolar bone resorption and Th1/Th17‐associated immune response triggered during Aggregatibacter actinomycetemcomitans‐induced experimental periodontitis are serotype‐dependent. Issue 10 (20th August 2018) - Monasterio, Gustavo; Castillo, Francisca; Ibarra, Juan Pablo; Guevara, José; Rojas, Leticia; Alvarez, Carla; Fernández, Baltasar; Agüero, Amaru; Betancur, Daniel; Vernal, Rolando
Abstract: Background: Aggregatibacter actinomycetemcomitans expresses several virulence factors that may contribute to the pathogenesis of periodontitis. Based on the antigenicity of the O‐polysaccharide component of the lipopolysaccharide (LPS), different A. actinomycetemcomitans serotypes have been described. Among them, serotype b has demonstrated a stronger capacity to trigger Th1 and Th17‐associated cytokine, CC‐chemokine, and CC‐chemokine receptor production on immune cells in vitro. With a murine model of experimental periodontitis, this investigation aimed to analyze the alveolar bone resorption and the pattern of immune response triggered by the different A. actinomycetemcomitans serotypes within periodontal lesions. Methods: For periodontal lesion induction, mice were orally infected with the different A. actinomycetemcomitans serotypes or their purified LPS. Alveolar bone resorption was analyzed using microcomputed tomography and scanning electron microscopy. Bacterial infection, receptor activator of nuclear factor‐kappa B ligand (RANKL) and Th1 and Th17‐associated cytokine, CC‐chemokine, and CC‐chemokine receptor levels were quantified by quantitative polymerase chain reaction (qPCR). T lymphocytes isolated from periodontal lesions were analyzed by flow cytometry. Results: In periodontal lesions, serotype b of A. actinomycetemcomitans induced higher alveolar bone resorption and expression of RANKL compared with the other serotypes. In addition, serotype b induced greater levels of Th1‐ and Th17‐related cytokines, CC‐chemokines, and CC‐chemokine receptors than the others. Similarly, higher numbers of infiltrating Th1 and Th17 lymphocytes were detected in serotype b ‐induced periodontal lesions. Conclusions: These results demonstrate that periodontal lesions induced with different A. actinomycetemcomitans serotypes elicited distinct alveolar bone resorption and immune response. In particular, serotype b was more pathogenic than the others and induced stronger Th1 and Th17 patterns of immune responses during experimental periodontitis.